Accounting Standards and Insurer Solvency Assessment - Windsor, Peter (IMF Working Papers; Working Paper ;, 2020)
The paper explores the use of accounting standards for insurer solvency assessment in the context of the implementation of IFRS 17. The paper is based on the results of a survey of 20 insurance supervisors. Overall, IFRS 17 is a welcome development but there will be challenges of implementation. Not many insurance supervisors currently intend to use IFRS 17 as a basis for solvency assessment of insurers. Perceived shortcomings can be overcome by supervisors providing clear specifications where the principles-based standard allows a range of approaches. Accounting standards can provide a ready-made valuation framework for supervisors developing new solvency frameworks.